2018
DOI: 10.3390/jfb9040071
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Characteristics of Titanium after Treatment of Chorreated Surface, Passive Acid, and Decontamination with Argon Plasma

Abstract: (1) Background. Titanium is characterized by its biocompatibility, resistance to maximum stress, and fatigue and non-toxicity. The composition, surface structure, and roughness of titanium have a key and direct influence on the osseointegration processes when it is used in the form of dental implants. The objective of the present study is to characterize, at chemical, superficial, and biological levels, the result of the application of the sandblasted with large-grit and acid-etched (SLA) treatment consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…Because of its decontaminating properties, argon plasma (Ar), which is widely used as a coagulant in digestive surgery [ 73 ], has been proposed by certain authors [ 52 , 74 , 75 , 76 , 77 ] to improve early integration of Ti implants due to its decontaminating properties.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its decontaminating properties, argon plasma (Ar), which is widely used as a coagulant in digestive surgery [ 73 ], has been proposed by certain authors [ 52 , 74 , 75 , 76 , 77 ] to improve early integration of Ti implants due to its decontaminating properties.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we have carried out an in vitro and in vivo study to compare two different surfaces in titanium grade IV and titanium grade V. The surface studied had undergone grit blasting treatment with alumina and double acid passivation for the modification of roughness. The treatment and its characteristics can be consulted in other publications of our group [20].…”
Section: Discussionmentioning
confidence: 99%
“…For the in vitro study, four groups were established to study titanium discs made of treated and untreated TiIV (TiIVT and TiIVNT) and treated and untreated TiV (TiVT and TiVNT). In previous studies published by our group, a greater description of the surface used and the control material used can be found [20].…”
Section: Preparation Of the Titanium Discmentioning
confidence: 99%
“…Treatment with SLA (sand-blasted, large-grit, acid-etched) was based on coarse grain (250 to 500 mm) silicon particles blasted following an acid etching treatment using a mixture of hydrochloric and sulphuric acids on the titanium surfaces, obtaining a surface roughness (R a ) of 1.5 ± 0.2 µm [16].…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have reported the advantages of this technique when it is applied for a few minutes before implant material utilization. This technique also yielded improved cell adhesion and protein adsorption in in vitro studies [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%